A review of the Colletes succinctus-group (Hymenoptera: Colletidae) from China with redescription of the male of C. gigas - Niu, Ze-Qing; Kuhlmann, Michael; Zhu, Chao-Dong (Zootaxa, 2013)
Four species of the Colletes succinctus-group known from China are reviewed and a key to species is provided. Colletes gigas Cockerell, 1918 is recognized as a member of the Colletes succinctus-group for the first time based on a redescrip-tion of the male.